2018
DOI: 10.1111/hepr.13259
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in medical management of hepatocellular carcinoma

Abstract: Transcatheter arterial therapies for hepatocellular carcinoma (HCC) have developed during the last decade. A fine powder formulation of cisplatin and the new platinum agent miriplatin became standard medicines in addition to anthracyclines in transcatheter arterial chemoembolization (TACE) in Japan. Recent prospective and retrospective studies supported the usefulness of platinum agents as a chemotherapeutic at the time of varied TACE therapy. Although balloon-occluded TACE is an effective therapy for localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 108 publications
0
57
0
Order By: Relevance
“…In the near future, several other promising second‐line agents, such as cabozantinib, ramucirumab, nivolumab, and pembrolizumab, will become available in the clinical setting for patients refractory or intolerant to sorafenib. The post‐progression survival (PPS) of patients who are refractory or intolerant to sorafenib is expected to improve by switching from sorafenib to second‐line therapy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the near future, several other promising second‐line agents, such as cabozantinib, ramucirumab, nivolumab, and pembrolizumab, will become available in the clinical setting for patients refractory or intolerant to sorafenib. The post‐progression survival (PPS) of patients who are refractory or intolerant to sorafenib is expected to improve by switching from sorafenib to second‐line therapy …”
Section: Introductionmentioning
confidence: 99%
“…The post-progression survival (PPS) of patients who are refractory or intolerant to sorafenib is expected to improve by switching from sorafenib to second-line therapy. [7][8][9] However, not all patients who are refractory or intolerant to sorafenib can be switched to second-line therapy. [10][11][12][13][14] Because the efficacy and safety of regorafenib in patients who do not meet the eligibility criteria for the RESORCE trial have not been verified, the Japan Clinical Practice Guidelines for Hepatocellular Carcinoma 2017 and the Barcelona Clinic Liver Cancer (BCLC) Guidelines for Hepatocellular Carcinoma 2018 recommended regorafenib as second-line treatment for patients tolerant to sorafenib and well-preserved liver function (Child-Pugh A) after radiologic PD with sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter arterial chemoembolization (TACE) is a standard therapy for unresectable HCC, especially for patients with BCLC B . Several studies have shown that TACE significantly improves patient survival compared to the best supportive care and can prolong survival in patients with multiple HCC tumors and no macrovascular invasion .…”
Section: Introductionmentioning
confidence: 99%
“…However, clinically, sorafenib has either not significantly increased survival or only increased survival by 2.8 months in advanced HCC patients . More recently, some new TKI drugs have been reported to be effective for advanced stage HCC in phase III studies: lenvatinib as the first line of therapy, and regorafenib as second‐line therapy . As a current research hotspot, blockade of cytotoxic T lymphocyte‐associated protein 4 and programmed cell death protein 1 (PD‐1)/programmed cell death ligand 1(PD‐L1) are the two most studied for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…3 More recently, some new TKI drugs have been reported to be effective for advanced stage HCC in phase III studies: lenvatinib as the first line of therapy, and regorafenib as second-line therapy. 4,5 As a current research hotspot, blockade of cytotoxic T lymphocyte-associated protein 4 and programmed cell death protein 1 (PD-1)/ programmed cell death ligand 1(PD-L1) are the two most studied for HCC. Nivolumab, an anti-PD-1 antibody, received expedited FDA approval for the treatment of advanced HCC after failure or intolerance to sorafenib in 2017.…”
Section: Introductionmentioning
confidence: 99%